2013
DOI: 10.1002/sca.21073
|View full text |Cite
|
Sign up to set email alerts
|

Topographic and ultrastructural variations in isthmus segment of oviduct during oestrous cycle in Caprines

Abstract: In the present study, the morphological variations in the isthmus segment of goat (Capra hircus) oviduct were studied using scanning and ultrastructural techniques during luteal and follicular phases of oestrous cycle. Topographic analysis of the isthmus epithelium in the follicular phase demonstrated irregular distribution of ciliated cells on the epithelium. A few secretory cells possessed bulbous apical processes which were concealed by the cilia. Cyclic changes were noticed in the secretory cells of isthmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Female reproductive health largely depends upon the quality and quantity of the oocytes produced. Surprisingly, female fertility index gets largely influenced by the exposure of pesticides producing various reproductive alterations, induced through direct or indirect pathways (Sangha, Kaur, & Khera, ; Sharma, Singh, Bhardwaj, & Saini, ). In the present study, GLP, an OP herbicide, too was found to influence ovarian physiology by increasing the incidence of granulosa cells apoptosis in caprine antral follicles by modulating the antioxidant defense system at all the concentrations (0.1, 2.0, and 4.0 mg/ml).…”
Section: Discussionmentioning
confidence: 99%
“…Female reproductive health largely depends upon the quality and quantity of the oocytes produced. Surprisingly, female fertility index gets largely influenced by the exposure of pesticides producing various reproductive alterations, induced through direct or indirect pathways (Sangha, Kaur, & Khera, ; Sharma, Singh, Bhardwaj, & Saini, ). In the present study, GLP, an OP herbicide, too was found to influence ovarian physiology by increasing the incidence of granulosa cells apoptosis in caprine antral follicles by modulating the antioxidant defense system at all the concentrations (0.1, 2.0, and 4.0 mg/ml).…”
Section: Discussionmentioning
confidence: 99%
“…Reproduction, a critical factor in maintaining and improving the efficacy of animal production, depends largely on the functional anatomy of female reproductive tract that plays a key role in fertilization, transportation of oocyte from ovary to uterus and development of zygote (Lauschova, Sangha et al ., ; Tienthai et al ., ; Sharma et al ., ). The oviduct, derived embryonically from the cranial regions of the primitive mullerian ducts (Price et al ., ), is divisible in four major segments – fimbriae, infundibulum, ampulla and isthmus (Hafez, ; Sharma et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Reproduction, a critical factor in maintaining and improving the efficacy of animal production, depends largely on the functional anatomy of female reproductive tract that plays a key role in fertilization, transportation of oocyte from ovary to uterus and development of zygote (Lauschova, Sangha et al ., ; Tienthai et al ., ; Sharma et al ., ). The oviduct, derived embryonically from the cranial regions of the primitive mullerian ducts (Price et al ., ), is divisible in four major segments – fimbriae, infundibulum, ampulla and isthmus (Hafez, ; Sharma et al ., ). The importance of oviductal epithelium and its secretions have been emphasized in various studies of oviduct during estrous or menstrual cycle in mammals including human, monkey, cow, sheep and pig (Verhage et al ., ; Brenner et al ., 1969; Bjorkman and Fredricsson, ; Hadek, ).…”
Section: Introductionmentioning
confidence: 97%
“…The ovary is a dynamic organ during the reproductive cycle (Peng et al., ; Sharma, Singh, Bhardwaj, & Saini, ; Souza‐Fabjan et al., ), and the regulation of ovarian function is a complex process, which is tightly regulated and controlled by a multitude of genes and endocrine hormones (Fournier et al., ; Ganguly, Meur, & Ganguly, ; Garcia, Masot, Franco, Gazquez, & Redondo, ; Ranjan et al., ). Ovary plays an important role in the reproductive cycle of Capra hircus, and it is regulated by a variety of reproductive hormones and a large of genes complexly.…”
Section: Introductionmentioning
confidence: 99%